Improving Students’ English Writing Proficiency through Interactive Writing Technique - Lorie Mae P Coloquit; Luningning A Canabal; Mark Philip C Paderan (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2020)
One of the active skills required not only in the field of academe for students but also in the industry world with degree holder employees that cause predicament in both areas is writing. Writing is one of the hurdles of different companies with their degree holder employees. Similarly, in the context of the academe, it is also found by previous studies that students are coping in writing academic essays and other writing outputs. The study aims to determine the effectiveness of interactive writing technique in intensifying basic writing skills to produce competent employees both in the academe and in the business world. This study also sought to address the predicament of students’ and employees’ low-level proficiency in basic writing. Interactive Writing is a collaborative technique used to enhance the level of proficiency when it comes to the organization of ideas, diction, elaboration, support and writing mechanics. Purposively, using these objectives: To investigate the level of English major’s writing proficiency in pre-test and post-test along with content, mechanics, organization, diction, elaboration, and support; to identify the level of effectiveness of the interactive technique and be able to establish an output based on the research findings. The study used a mixed-method design. Three phases of data gathering procedure were employed namely; pre-test, intervention, and post-test. Pre-test and Post-test were compared using the t-test and analyzed using the Error Density Index of Malicsi (2018). Results of the study unveil that students writing in the post-test improved from the pre-test general weighted mean of 2.28 interpreted as